The role of physical and occupational therapy in palliative and hospice medicine of neurodegenerative diseases - O. M. Raznatovska; S. M. Kanyhina; O. S. Shalmin; O. O. Cherepok (Zaporozhye State Medical University, 2023)
The aim of our research is to review modern literature regarding the relevance and frequency of physical and occupational therapy in palliative and hospice medicine of neurodegenerative diseases. Results. The role of physical therapy and occupational therapy in palliative-hospice medicine for such neurodegenerative diseases as Parkinson's disease, cognitive impairment and/or dementia, Alzheimer's disease, amyotrophic lateral sclerosis, multiple sclerosis has been studied. It has been found, a wide variety of physical and occupational therapy is widely used in palliative hospice medicine despite the disease's severity. These methods significantly improve the quality of life of both palliative patients and their families ultimately. Physical and occupational therapist specialists are a very important link in the multidisciplinary team of palliative-hospice medicine. Conclusions. Physical and occupational therapy play a very important role in neurodegenerative diseases patients requiring palliative-hospice care in today's world. Palliative physical and occupational therapy of patients with neurodegenerative diseases has many benefits that help maintain or improve various bodily functions. This contributes to the quality of life improving for not only patients but also for their family members who care for them.